2014
DOI: 10.1111/jfpp.12205
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L actobacillus Plantarum  DM616 on Dough Fermentation and Chinese Steamed Bread Quality

Abstract: This study investigated the effect of Lactobacillus plantarum DM616 on dough fermentation for making Chinese steamed bread. Dough fermentation was carried out via inoculation with Saccharomyces cerevisiae as monoculture, or in combination with L. plantarum DM616 as co-culture. The presence of L. plantarum DM616 caused faster depletion of reducing sugars and had little effect on the maximum specific growth rate (μmax) and final cfu/g sourdough of S. cerevisiae. In co-culture, the pH of the dough varied from 3.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Figure 3 shows the scanning electron micrograph of control bread samples with two magnifications of ×150 and ×550. As expected and was shown in previous studies, starch granules were presented in the form of small and large spherical and ovoid granules [48]. Higher amounts of sourdough resulted in the larger holes and open structure (Figures 3(c) and 3(d)).…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 88%
“…Figure 3 shows the scanning electron micrograph of control bread samples with two magnifications of ×150 and ×550. As expected and was shown in previous studies, starch granules were presented in the form of small and large spherical and ovoid granules [48]. Higher amounts of sourdough resulted in the larger holes and open structure (Figures 3(c) and 3(d)).…”
Section: Scanning Electron Microscopy (Sem)supporting
confidence: 88%
“…The steamed bread prepared by the remixed fermentation dough showed higher whiteness. The improved whiteness of the steamed bread may be due to the changed interior microstructure and composition (Li, Li, Deng, Bian, et al, 2014). Based on the data shown in Table 1, it seems that the remixed fermentation dough would be appropriate for the improved chewiness and whiteness.…”
Section: Effects Of the Amount Of Remixed Flour On The Steamed Bread mentioning
confidence: 97%
“…Hardness and chewiness of the crumb was performed using a Texture Analyzer (TA.XT2i, Stable Micro Systems, Ltd., Godalming, UK) equipped with a 35 mm diameter aluminum cylindrical probe with pre-test speed 1 mm/s, test speed 5 mm/s, post-test speed 5 mm/s and trigger force 5 g. The deformation level was 75% of the sample height. Steamed bread specific volume was measured using the rape seed displacement method and the whiteness was determined by whiteness meter (WGB-IV, TASAN Co. Ltd., Hangzhou, China) (Li, Li, Deng, Bian, & Liu, 2014;Sim, Noor Aziah, & Cheng, 2011).…”
Section: Steamed Bread Evaluationmentioning
confidence: 99%
“…It has been determined that L. plantarum strain LD4 ribosomally synthesises antimicrobial peptides, which have potential applications in enhancing bread safety (Kumar et al ., ). It has also been observed that L. plantarum strain VTT inhibited the growth of Bacillus subtilis and Bacillus lichenformis in wheat bread (Katina & Sauri, ), L. plantarum strain FST 1.7 inhibited growth of Fusarium species in wheat bread (Dal Bello et al ., ), L. plantarum strain DM616 reduced the hardness and increased whiteness of steamed bread (Li et al ., ), and L. plantarum strain PON100148 used in sourdough fermentation produced high concentrations of organic acids and increased bread quality parameters (Ventimiglia et al ., ).…”
Section: Introductionmentioning
confidence: 99%